Pengaruh Aplikasi TikTok dalam Komunikasi Generasi Z: Tinjauan terhadap Perubahan Pola Interaksi dan Ekspresi Digital - Evanti Andriani; Adam Dista Prasetya; Bagas Yudha Pratama (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2024)
This research investigates the impact of using the TikTok application on the communication patterns of Generation Z. TikTok has become a significant platform for this generation in conveying their expressions and interactions through creative video content. This study aims to explore how these applications influence the way Generation Z communicates, including changes in their digital self-expression. This research uses a qualitative approach to analyze how TikTok influences the dynamics of interpersonal communication, the use of visual language, and content consumption and production patterns in the current digital cultural context.